До 80-річчя від дня народження Сергiя Михайловича Рябченка - Bakai, O. S.; Bar’yakhtar, V. G.; Galkina, O. G.; Lozenko, A. F.; Loktev, V. M.; Pashitskii, E. A.; Semenov, O. V.; Sugakov, V. Y.; Yatskiv, Ya. S.; Zagorodny, A. G. (Publishing house "Academperiodika", 2020)
-